Stereoselective synthesis of sulfonated 1-indenones via radical-triggered multi-component cyclization of β-alkynyl propenones. Issue 5 (4th December 2017) - Shen, Zheng-Jia; Wu, Ya-Nan; He, Chun-Lan; He, Long; Hao, Wen-Juan; Wang, Ai-Fang; Tu, Shu-Jiang; Jiang, Bo
Abstract : New radical-triggered multi-component cyclizations of β-alkynyl propenones have been developed, leading to 50 examples of sulfonated 1-indenones with generally good yields and high levels of stereoselectivity. Abstract : New radical-triggered multi-component cyclizations of β-alkynyl propenones have been developed, leading to 50 examples of sulfonated 1-indenones with generally good yields and high levels of stereoselectivity. The oxidant-free azosulfonylation of β-alkynyl propenones with aryldiazonium salts and DABSO was realized under the neutral–redox conditions where TBHP enabled the direct selenosulfonylation of β-alkynyl propenones by combining sulfinic acids and diphenyl diselenide. This protocol features a broad substrate scope, high functional group tolerance and mild reaction conditions.